ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP KINERJA - Arisandi, Devy; Thaha, Atifah; Chusnah, Chusnah (Kinerja, 2019)
Increasing public awareness about the health of the strong competition in the business world, especially the health of their field laboratorium.Never measurement of customer satisfaction, this is the basic of this research is finding a match between the interest rate the elements of service according to the customer with the work done by the company. The study was conducted in the Clinical Laboratory Westerindo Jakarta with 340 respondents. Data collected through questionnaires covered. Analyses were performed using methods Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The result of CSI is 0723, where the value is in the category "Satisfied" on the performance conducted by the Clinical Laboratory Westerindo. Analysis of customer satisfaction was less satisfied with Tangible indicators (-0.58). Result from IPA respectively each mapped attribute in the Cartesian Diagram which 9 attributes located in quadrant I (20%) less satisfied, 13 attributes located in quadrant II (28.9%) very satisfied, 15 attributes located in quadrant III (33.3%) quite satisfied, 8 attributes located in quadrant IV (17.7%) satisfied. Recommendations addressed to the Clinical Laboratory Westerindo to pay attention to the gap and the weak attributes in each quadrant.